Medicinal Plants of Tadoba National Park - Giradkar, Pradnya G.; Yeragi, S. G. (Indian Forester, 2006)
This paper gives an account of 91 medicinal plants found in Tadoba National Park, Maharashtra State, India along with their local names, family, habit and medicinal uses in brief.